COMPARATIVE PHYTOCHEMICAL PROFILE OF CRINUM DEFIXUM KER-GAWLER LEAVES USING GC-MS - Elaiyaraja, A; Chandramohan, G (Journal of Drug Delivery and Therapeutics, 2018)
The present investigation was carried out to determine the possible phytochemical compounds present in the various extracts of Crinum defixum Ker-Gawler leaves. It is an important medicinal plant worldwide trends towards the utilization of natural plant remedies has created an enormous need for the use of medicinal plants. Different pharmacological properties of C.defixum Ker-Gawler have already been reported. Thus, the present study was performed to investigate the preliminary phytochemical screening, separation, identification of compounds and compare the phytochemical composition of various fractions of C.defixum Ker-Gawler leaves using gas chromatography-mass spectrometry. The plant was extracted for various solvents in increasing order of polarity from using n-hexane, chloroform, ethyl acetate, acetone, ethanol, butanol and methanol. The extracts were subjected to GC-MS analysis and also confirmed by spectral analysis. Keywords: Crinum defixum Ker-Gawler, Phytochemical screening, Separation and identification of compounds, GC-MS, Spectral analysis.